Exchange-bias features in nanoceramics prepared by spark plasma sintering of exchange-biased nanopowders. Issue 17 (6th April 2020) - Franceschin, Giulia; Gaudisson, Thomas; Perez Quiros, Sonia; Yaacoub, Nader; Grenèche, Jean-Marc; Menguy, Nicolas; Mercone, Silvana; Mazaleyrat, Frédéric; Ammar, Souad
Abstract : The evolution of the exchange bias at room temperature is studied between a nanopowder and its ceramic counterpart. Abstract : Conventional methods for sintering magnetic biased granular solids are generally known to induce severe grain growth and coarsening, thus making any evidence of exchange bias (EB) hard to detect in the resulting consolidates. This work explores the possibility of preparing a hetero-nanoconsolidate starting from an exchange-biased nanopowder and using Spark Plasma Sintering (SPS), in order to overcome that microstructural limitation. It also investigates the capability of the resulting solid to establish EB. The nanopowder consists of an intimate nanocrystalline mixture of the antiferromagnetic NiO and ferrimagnetic CoFe2 O4 phases. It exhibits a significant broadening of the hysteresis loop at room temperature when measured under field cooling (FC) conditions. X-ray diffraction coupled to high resolution transmission electron microscopy and 57 Fe Mössbauer spectrometry shows that sintering induces a drastic atomic diffusion leading to the replacement of the starting NiO and CoFe2 O4 phases by their Ni1− x Co x O and Co1− x Ni x Fe2 O4 solid solutions ( x value close to 0.25). As a result, exchange-bias is hindered at 300 K but always expressed at lower temperatures, far below the Néel temperature of the new antiferromagnet. The maximum EB value for the ceramics is measured at 5 K and is calculated about 48 mT under a cooling magnetic field of 7 T. This value decreases when the temperature increases, but it remains different from zero up to 200 K.